Information technology traffic data in the banking system based on multi-matrix models - Vozna, Natalia; Davletova, Alina; Pituh, Igor (Видавництво Львівської політехніки, 2010)
The paper laid the information technology of motion data in the banking system based on multi-matrix models.
Keywords: information technology; distributed computer systems; model motion data; banking system